An antigen detection assay for diagnosing filariasis - Wongkamchai S. (2014)
In this study we examined the diagnostic potential of monoclonal antibodies (MAb) reactive to antigens of adult Brugia malayi, their microfilariae and antigen of Dirofilaria immitis. The MAb of clone 17E10, which were of IgM isotype, reacted to the inner cuticles and internal content of both male and female worms and also to the sheath and internal content of microfilariae in utero. However, these MAb did not react to the sheath of blood circulating microfilariae. The MAb 17E10 produced a smear pattern between 37 to > 200 kDa in the Western blot analysis against a SDS-PAGE separated extract of B. malayi. The epitopes were non-protein in nature as indicated by their resistance to proteinase-K treatment. The MAb 17E10 were applied in a sandwich ELISA to detect filarial antigen in the buffy coat and plasma of patients. We tested patients with different clinical manifestations of brugian filariasis, i.e. microfilaremia (M), lymphangitis (L) and elephantiasis (E), as well as non-symptomatic inhabitants of a filariasis endemic area (NE), and compared them to samples from non-symptomatic inhabitants of disease non-endemic areas (NNE). It was found that 22 of 31 (70.9%) of M, 7 of 13 (53.8%) of L, 2 of 14 (14.2%) of E, 10 of 100 (10.0%) of NE and none (0%) of the NNE were positive for antigenaemia. The assay was also positive in 14 of 15 (93.3%) blood samples from B. malayi microfilaremic cats and in 7 of 7 (100%) blood samples of Dirofilaria immitis microfilaremic dogs. The so-developed test has a high potential for routine diagnosis of active filariasis, for epidemiological studies in both humans and reservoir animals and for monitoring treatment efficacy.